Modelling Motivational Dynamics: Demonstrating When, Why, and How We Self-Regulate Motivation - Joanne Hudson (Journal of Motivation, Emotion, and Personality: Reversal Theory Studies, 2019)
Motivation quality affects the initiation and maintenance of behavior and physical and psychological health. Despite this, we understand little about how situational fluctuations occur and are regulated. In this paper we analyze the utility of applying basic psychological needs theory (a sub theory of self-determination theory) and reversal theory as frameworks for understanding motivational dynamics. Specifically, we posit a causal model linking acute consequences of need satisfaction and the purpose and direction of meta-motivational state shifts. This model is tested in two sequential experiments, demonstrating: (i) that thwarting or satisfying psychological needs increases meta-motivational reversal frequency and (ii) that individuals use meta-motivational shifts to compensate for imbalances in need satisfaction. Broad-ranging implications include informing therapeutic support for preventing maladaptive emotions and behaviors and promoting psychological health and well-being. In respect to modelling the dynamics of human motivation, this study adds clarity to understanding when (following need deprivation), why (to regain and balance need satisfaction), and how (through changing metamotivational states) we self-regulate.